Pelatihan Peningkatan Kompetensi Komputer dan Literasi Digital untuk Siswa SMK - Dita Rahmawati; Wahyudi Syaputra; M Bambang Purwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Activity (Pengmas) is a form of contribution by lecturers and students in supporting the improvement of digital literacy among vocational high school students, especially students of SMK Negeri 2 Palembang. The main objective of this activity is to equip students with basic knowledge and practical skills in computerization and digital, including software introduction, basic coding, software installation, and simple video editing. The implementation method uses a hands-on training in a computer laboratory, involving two lecturers and several students as facilitators. The activity results showed increased students' interest and understanding of the material presented and active interaction during the training. The school welcomes this activity and hopes to establish sustainable cooperation with higher education institutions. This community service is expected to become a model of educational activities relevant to the needs of the world of work in the digital era and positively impact the competence of vocational school students in facing future challenges.